2017
DOI: 10.15252/embr.201642573
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ubiquitin ligase RNF 114 and TAB 1 degradation are required for maternal‐to‐zygotic transition

Abstract: The functional role of the ubiquitin-proteasome pathway during maternal-to-zygotic transition (MZT) remains to be elucidated. Here we show that the E3 ubiquitin ligase, Rnf114, is highly expressed in mouse oocytes and that knockdown of Rnf114 inhibits development beyond the two-cell stage. To study the underlying mechanism, we identify its candidate substrates using a 9,000-protein microarray and validate them using an in vitro ubiquitination system. We show that five substrates could be degraded by RNF114-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 41 publications
(42 reference statements)
3
43
0
Order By: Relevance
“…It has been reported that RNF114 is ampli ed and upregulated in patients with psoriasis but downregulated in the testes of azoospermic patients compared with its level in fertile adult testes [33], suggesting that it may be involved in human diseases, although the underlying molecular mechanism remains largely unde ned. RNF114 substrates that have been reported include P21, which is involved in cell cycle regulation [22], TAB1 involved in maternal-to-zygotic transition [34] and A20 involved in NF-κB activity and T cell activation [35]. In this study, we demonstrated PARP10 as a newly identi ed RNF114 substrate.…”
Section: Discussionsupporting
confidence: 52%
“…It has been reported that RNF114 is ampli ed and upregulated in patients with psoriasis but downregulated in the testes of azoospermic patients compared with its level in fertile adult testes [33], suggesting that it may be involved in human diseases, although the underlying molecular mechanism remains largely unde ned. RNF114 substrates that have been reported include P21, which is involved in cell cycle regulation [22], TAB1 involved in maternal-to-zygotic transition [34] and A20 involved in NF-κB activity and T cell activation [35]. In this study, we demonstrated PARP10 as a newly identi ed RNF114 substrate.…”
Section: Discussionsupporting
confidence: 52%
“…The TAB1 kinase inhibits the action of the NFκB transcription factor by retaining it in the cytoplasm. In early embryos, the E3 ubiquitin ligase RnF114 directs degradation of TAB1, permitting translocation of NFκB into the nucleus and, thus, activation the NFκB pathway, which is essential for development (Yang et al, 2017). Indeed, either knockdown of RnF114 or persistence of TAB1 protein prevents development beyond the two-cell stage (Yang et al, 2017).…”
Section: Post-translational Regulation Of Maternal Proteinsmentioning
confidence: 99%
“…Previous studies have shown that RNF114 expression is elevated at late G1 phase to regulate p21 and p57 levels and is crucial for G1-to-S phase transition 48 . Other RNF114 substrates that have been reported include TAB1 involved in maternal-to-zygotic transition and A20 involved in NF-kB activity and T cell activation 57,58 . In cancer contexts or other cell and tissue types, nimbolide may thus have additional activities through regulating the levels of other RNF114 protein substrates.…”
Section: Discussionmentioning
confidence: 99%